DISAGGREGATED EFFECTS OF INFANT AND ADULT MORTALITY ON ECONOMIC GROWTH IN NIGERIA - ESARA, ESTHER; GWANDZANG , CHARITY ISA; ZACHARIAH, EMMANUEL; CHINANUIFE , EMMANUEL (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study is the empirical investigation of the effects of infant and adult mortality on economic growth. The effects are disaggregated into these age specific mortalities. The objective is to assess the disaggregated effect of mortalities in adults and infants on economic growth in Nigeria. We used Descriptive analysis with Secondary data on the Nigerian economy mostly from 1983 to 2023 and the Auto Regressive Distributed Lag (ARDL) technique to embark on the study. The disaggregated estimations (respective estimations) and analysis reveal that mortality in adults has a negative and significant effect on the growth of the Nigerian economy both in the short and long run, but infant mortality has a positively significant effect in the short run and a negative effect in the long run. Therefore, we recommend that government spending on health should be increased efficiently, the economic condition of the populace should be improved by providing more job opportunities to increase labour participation and income and a holistic approach should be taken to reduce adult and infant mortality rate